Comparative Study of Soil Grouting with Cement Slurry and Cement-Sodium Silicate Slurry. (18th February 2018) - Zhu, Mingting; Zhang, Qingsong; Zhang, Xiao; Hui, Bing
Abstract : Cement slurry and cement-sodium silicate slurry are most widely applied for soil grouting reinforcement project. The viscosity change of cement slurry is negligible during grouting period and presumed to be time independent, while the viscosity of cement-sodium silicate slurry increases with time quickly and is presumed to be time dependent. Due to the significant rheological differences between them, the grouting quality and the increasing characteristics of grouting parameters may be different. Those are main factors for grouting design. In this paper, a large-scale 3D grouting simulation device was developed to simulate the surrounding curtain grouting for a tunnel. Two series of surrounding curtain grouting experiments under different initial pressures of 100 kPa, 150 kPa, and 200 kPa were performed. The overload test on the tunnel was performed to evaluate the grouting quality of all surrounding curtain grouting experiments. The results show that the increasing trend of grouting pressure for cement-sodium silicate is similar to its viscosity; the setting time of cement-sodium silicate slurry obtained from the laboratory test is less than that in the practical grouting environment where grout slurry solidifies in soil; the grouting quality of cement-sodium silicate slurry is better than cement slurry, and the grouting quality decreases with initial pressure.